Blended learning dalam pendidikan jasmani: Strategi integratif untuk meningkatkan kreativitas dan keterampilan problem solving - Mustikaningrat, Gregorius Andrea; Sulastri, Augustina (Physical Education Departement of University PGRI Jombang, 2025)
Physical Education. The shift in learning approaches in the digital era has encouraged teachers to combine online and offline methods to enhance student engagement and learning effectiveness. Using a systematic literature review method, this study analyzes 15 national and international scientific articles published over the last five years (2019–2024), which discuss the implementation of blended learning in Physical Education and its impact on students' cognitive aspects. The analysis shows that blended learning can enhance student creativity by providing space for independent exploration through digital media and collaborative work during offline activities. Students become more confident in expressing ideas and creative solutions when facing challenging learning situations. Furthermore, this approach has proven effective in developing problem-solving skills through project-based and contextual case study learning. Active student involvement in formulating, testing, and evaluating solutions plays a crucial role in the learning process. Overall, blended learning offers a flexible and adaptive approach in Physical Education, not only improving physical skills but also strengthening students' cognitive development. Therefore, teachers are encouraged to design learning strategies that integrate technology with physical activities to achieve more holistic learning outcomes